Screening for Heme Oxygenase Enzyme among Clinical Isolates of Escherichia Coli Isolated from Urine Sample - Murtadha K. Alkreami (Journal of Global Pharma Technology, 2016)
A total of (150) urine sample were obtained from different patient which is (male, female and pediatric) who are suffering from urinary tract infection and are using catheter indwelling, who are admitted to the merjan teaching hospital in Hilla city for a period rang from (July to September 2018), only 36 isolates (24%) were diagnosis as E. coli. Three genes related to heme oxygenase production and transported are studied. These genes are (chuA, chuS and chuT) and the result showed that 26 isolates (90%) from total sample carry chuA in genetic marker and 25 isolates (85%) from total sample carry chuS in genetic marker and only 18 isolates (58%) from total sample carry chuT in genetic marker, and the total positive results of isolates which carry all these three genetic marker in genomic material is only 15 isolates. These (15) isolates were undergone for induction and production of HO-1 enzyme, through detection of beliverdin in chochlate agar and also through estimation free iron spectrophotometrically. The results showed that all isolates gave positive results for enzyme production through production of biliverdin and high levels of free iron when compared to control groups.  Moreover, two different antibiotics are used to show their effect on enzyme activity, and the results revealed that neomycin and ciprofloxacin have an effect on enzyme activity in the presence of imidazole buffer.